ANALISIS PERFORMA LIGHTWEIGHT CRYPTOGRAPHY PADA ESP32: STUDI KOMPARATIF ASCON-128, TINYJAMBU, DAN GIFT-COFB UNTUK KEAMANAN DATA SENSOR IoT - Muhammad Baso Adrian Ibrahim; Dwi Prianto; Imelda Imelda (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The Internet of Things (IoT) has become the cornerstone of modern digital infrastructure, connecting billions of devices with limited computational resources. Data security on IoT devices presents a critical challenge given the constraints in memory, power, and processing capabilities. This study presents a comprehensive comparative analysis of three algorithms from the NIST LWC Standardization process—ASCON-128 (official NIST standard, 2023), TinyJAMBU, and GIFT-COFB—implemented on the ESP32 microcontroller based on the Xtensa LX6 dual-core 240 MHz architecture. Testing was conducted with 10,000 iterations across four primary metrics: encryption throughput (kbps), operational latency (µs), memory consumption (RAM and Flash), and energy efficiency (nJ/operation). Experimental results demonstrate that ASCON-128 achieves the highest throughput of 7,035.10 kbps with the lowest energy consumption per operation of 9.6 nJ/operation, making it the optimal solution for IoT devices that offers the best balance between cryptographic security and performance. TinyJAMBU demonstrates a significant advantage in RAM efficiency, requiring only 4 bytes of stack memory, making it the preferred choice for ultra-constrained IoT devices. Meanwhile, GIFT-COFB offers superior resistance to side-channel attacks among the three evaluated algorithms. This research produces algorithm selection criteria based on resource profiles and device security requirements as a technical reference for IoT system developers in making decisions on measurable and accountable cryptography implementation.